Light-regulated morphology control in supramolecular polymers - Mukherjee, Anurag; Ghosh, Goutam (Nanoscale, 2024)
Stimuli-responsive materials have gained significant recent interest owing to their versatility and wide applications in fields ranging from materials science to biology. In the majority of examples, external stimuli, including light, act as a remote source of energy to depolymerize/deconstruct certain nanostructures or provide energy for exploring their functional features. However, there is little emphasis on the creation and precise control of these materials. Although significant progress has been made in the last few decades in understanding the pros and cons of various directional non-covalent interactions and their specific molecular recognition ability, it is only in the recent past that the focus has shifted toward controlling the dimension, dispersity, and other macroscopic properties of supramolecular assemblies. Control over the morphology of supramolecular polymers is extremely crucial not only for material properties they manifest but also for effective interactions with biological systems for their potential application in the field of biomedicine. This could effectively be achieved using photoirradiation which has been demonstrated by some recent reports. The concept as such offers a broad scope for designing versatile stimuli-responsive supramolecular materials with precise structure-property control. However, there has not yet been a compilation that focuses on the present subject of employing light to impact and regulate the morphology of supramolecular polymers or categorize the functional motif for easy understanding. In this review, we have collated recent examples of how light irradiation can tune the morphology and nanostructures of supramolecular polymers and categorized them based on their chemical transformation such as cis - trans isomerization, cycloaddition, and photo-cleavage. We have also established a direct correlation among the structures of the building blocks, mesoscopic properties and functional behavior of such materials and suggested future directions. The morphology of supramolecular assemblies equipped with photoresponsive units can be altered by light. In this review, we have covered current examples of nanostructures and morphology of supramolecular polymers that are tuned via photoirradiation.